New U-Pb constraints and geochemistry of the East Kirkton Quarry, Scotland: Implications for early tetrapod evolution in the Carboniferous - Hector K. Garza; Elizabeth J. Catlos; Thomas J. Lapen; Julia A. Clarke; Michael E. Brookfield (PLoS ONE, 2025)
The transition of vertebrates from aquatic to terrestrial environments during the late Devonian to early Carboniferous marks a crucial evolutionary milestone. However, this transition remains poorly understood due to a scarcity of early tetrapod fossils during the late Devonian to early Mississippian, creating a gap in the fossil record known as Romer’s Gap (~360–345 Ma). Recent discoveries have narrowed this gap, providing critical insights into early tetrapod evolution. The East Kirkton Quarry in Scotland’s Midland Valley, has yielded tetrapod fossils considered early stem amphibians and amniotes. They have been proposed to be Mississippian (early Carboniferous) in age, yet data to inform their precise ages remain limited. Here, zircon grains from two tuffaceous clastic limestones and shales were dated using Laser Ablation-Inductively Couple Plasma-Mass Spectrometry (LA-ICP-MS). The study presents detrital zircon U-Pb dates, which refine the current biostratigraphy ages assigned to Westlothiana lizziae, Silvanerpeton miripedes, Balanerpeton woodi, Ophiderpeton kirktonense, Eucritta melanolimnetes, and Kirktonecta milnerae to a maximum depositional age (MDA) of 341 ± 3 Ma (±2σ, n= 7 dates), placing them in the middle-lower Visean (Holkerian-Arundian) rather than the previous assigned upper Visean (Brigantian). This revised maximum depositional age places the East Kirkton Quarry fossils within the older, critical interval of Romer’s Gap, bridging a significant evolutionary time interval in the Mississippian fossil record, and allows for refining future tetrapod time trees. X-ray Fluorescence and X-ray Diffraction analyses reveal heterogeneity in the lower East Kirkton Limestone of the East Kirkton Quarry, with variations in elemental and mineralogical compositions, reflecting episodic volcanic and detrital inputs and hydrothermal activity.